A study on factors that influence PP(T)SB’S workers in making personal investments decision / Mohd Sahhamin Abd Hamad - Abd Hamad, Mohd Sahhamin (Bachelor Of Business Administration (Hons) Marketing, 2015)
This research investigates the factors that influence employees of PETRONAS Refinery (Terengganu) Sdn. Bhd. in making personal investments decision. The literature provided discusses the three independent variables which are rate of return, future planning awareness and accounting information and the dependent variable is personal investments decision. The study aims at identifying the most significant factors that influencing in making personal investments decision. The project based on descriptive research design. The data was collected with the help of questionnaire in previous research. The questionnaire included Section A which covered demographic information and Section B to cover all variables which are personal investments decision, rate of return, future planning awareness and accounting information. Questions in Section B used 5 point Likert Scale. The sample size considered for the study was 120 wherein the entire sample was working with PETRONAS Refinery (Terengganu) Sdn. Bhd. from several departments. The software used for the analysis of the findings was SPSS (Statistical Package for Social Sciences) Version 20.0. Correlation analysis showed that there are positively relationship between all the dependent variables (rate of return, future planning awareness and accounting information) and personal investments decision. The findings from T-Test showed that all the independent variables were significant to the dependent variable